Introduction of Augmented Reality to Create Interactive Learning Media for Teachers in Purwakarta - Dewi Indriati Hadi Putri; Haffiyan Putra Pratama; Ichwan Nul Ichsan; Diky Zakaria; Makna A’raaf Kautsar; Diana Eka Putri (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
Utilization of educational media using Augmented Reality (AR) technology can stimulate students’ mindset in thinking critically about problems and events that exist in everyday life. The use of educational media with augmented reality directly can helps students learn wherever and whenever they want. In order to facilitate knowledge sharing, a community service activity was carried out by the UPI Telecommunication Systems Study Program, Purwakarta Campus, to introduce AR technology and train teachers to be able to create interactive technology-based learning media. The results obtained show that 1) participants are very satisfied with the content of the material with a percentage of 90.3% which means good; 2) the method of delivery of the workshop material by the presenters is considered good with a percentage of 89% and 3) according to the participants the activity of making the AR program is very useful with a response percentage of 93%.